Rhodium Germanide Schottky Barrier Contacts. (1st January 2015) - Lutzer, B.; Hummer, M.; Simsek, S.; Zimmermann, C.; Amsuess, A.; Hutter, H.; Detz, H.; Stoeger-Pollach, M.; Bethge, O.; Bertagnolli, E.
Abstract : Rhodium Schottky barrier contacts on germanium substrates are investigated in terms of electrical, physical, and chemical properties. The Rh, deposited by electron beam evaporation on a n-type (100)-Ge substrate, has been annealed in N2 H2 at different temperatures ranging from 450°C up to 800°C. Rh/Ge Schottky diodes were fabricated to extract the Schottky barrier height, the ideality factor as well as the forward to backward current ratio. By using various analyzing techniques such as Atomic Force Microscopy (AFM), X-ray Diffraction (XRD), Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS), and High-resolution Transmission Electron Microscopy (HR-TEM), the formation of polycrystalline Rh-germanide Rhx Gey phases has been proven. At 500°C germanidation temperature an effective SBH of 0.59 eV is extracted showing a high current ratio of 5 × 10 3 and a remarkable low ideality factor of 1.07.